1975
DOI: 10.1093/jnci/55.5.1079
|View full text |Cite
|
Sign up to set email alerts
|

Change of Antigenic Expression on Rat Tumor Cells After Their Transplantation

Abstract: Antigenic expression of 3-methylcholanthrene-induced transplantable fibrosarcoma KMT-17 cells was investigated in relation to days after ip transplantation. Cytotoxicity tests with antiserum against tumor-associated surface antigen of KMT-17 cells revealed that cytotoxic sensitivity and absorbing capacity decreased after transplantation, but they increased when other normal rats were given transplants of tumor cells. A decrease in the sensitivity was observed when immunosuppressively irradiated rats were given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Gotohda et al (1975) reported a change of antigenic expression of rat tumor cells after their transplantation. The authors observed a change of tumorassociated antigens while the histocompatibility antigens remained constant.…”
Section: Discussionmentioning
confidence: 99%
“…Gotohda et al (1975) reported a change of antigenic expression of rat tumor cells after their transplantation. The authors observed a change of tumorassociated antigens while the histocompatibility antigens remained constant.…”
Section: Discussionmentioning
confidence: 99%
“…Rat KMT-17 fibrosarcoma cells (Gotohda et al, 1975), induced by 3-methylcholanthrene in WKA rats, were maintained in ascites or solid form grown subcutaneously (s.c.) in WKAH/Hkm rats (Japan SLC, Hamamatsu, Japan). Tumor-derived endothelial cells (TEC) were isolated from the solid KMT-17 fibrosarcoma as described previously (Ohizumi et al, 1998) and cultured in Dulbecco's modified Eagle medium (DMEM) (GIBCO, Grand Island, NY) containing 10% fetal bovine serum (FBS) (GIBCO), 50 µg/ml endothelial cell growth supplement (ECGS; Becton Dickinson, Bedford, MA).…”
Section: Cells and Mabsmentioning
confidence: 99%
“…We have reported that immunization with xenogenized tumor cells, live tumor cells infected with murine leukemia viruses, produces strong antitumor immunity and is one possible method of active specific immunotherapy (Hosokawa et al 1971;Koba yashi et al 1969bKoba yashi et al , 1970. Gotohda et al (1974) reported that combination therapy with xenogenized tumor cells and chemotherapy and/or transfer of immune lymphocytes was effective in curing tumors actively growing in the host. In the present paper, the authors attempted to accelerate the inhibitory effect of the xenogenized tumor cells by combining treatment with cyclophosphamide and to study the role of cyclophosphamide on the immunogenicity of xenogenized tumor cells.…”
mentioning
confidence: 99%